Efficientcy of corrosion protection properties of epoxy resin/cashew nut shell liquid alloy reinforced with titanium dioxide - Loonpooht, Wilaivan; Tangtrakarn, Apishok; Kasemesiri, Pornnapa (Engineering and Applied Science Research, 2015)
The cure behavior of epoxy resin containing cashew nut shell liquid (CNSL) and corrosion protective performance of epoxy alloy reinforced with titanium dioxide (TiO2) have been investigated. According to FTIR spectra obtained from epoxy alloys, the CNSL can be employed as a curing agent. The curing process occurred when amount of CNSL was as low as 20%wt. It was found experimentally that the CNSL used for epoxy curing should not be higher than 40%wt.in order to minimize amount CNSL left after reaction. The corrosion protective performance of epoxy alloy on aluminum sheets was carried out. The results revealed that the ability of corrosion resistance increased with the amount of TiO2 introduced into the Epoxy/CNSL film investigated. In this work, the highest corrosion resistance value was found when the TiO2 concentration of 1.5 %wt was reached.